Matematică
sofi312
8

a) [latex] \frac{1}{4} [/latex]x-6=[latex] \frac{1}{3} [/latex](2-x)+[latex] \frac{1}{3} [/latex] b)2(x-3)+[latex] \frac{11}{2} [/latex] c)[latex] \frac{5}{6} [/latex](x-4)+x=[latex] \frac{1}{3} [/latex](x+2)-3 d)[latex] \frac{3}{8} [/latex](x+2)+[latex] \frac{x}{4} [/latex]=[latex] \frac{5}{6} [/latex](x-3)+2

+0
(1) Răspunsuri
genius31

x-6=(2-x)+ x/4-6=2/3-x/3+1/3 x/4+x/3=6+2/3+1/3 (3x+4x)/12=(6·12+2·4+1·4)/12 7x/12=(72+8+4)/12 7x=84 x=84/7=12 b)2(x-3)+ 2x-6+11/2=0 2x=6-11/2 2x=(12-11)/2 2x=1/2 4x=1 x=1/4 c)(x-4)+x=(x+2)-3 5x/6-20/6+x=x/3+2/3-3 5x/6+x-x/3=20/6+2/3-3 (5x+6x-2x)/12=(20+4-18)/6 9x=6 x=6/9=2/3 d)(x+2)+=(x-3)+2 3x/8+6/8+x/4=5x/6-15/6+2 3x/8+x/4-5x/6=-6/8-15/6+2 (9x+6x-20x)/24=(-18-60+48)/24 -5x=-30    (-1) x=30/5 x=6

Adaugă răspuns